Risk factors for asthma after infant bronchiolitis. Issue 4 (28th November 2017) - Törmänen, S.; Lauhkonen, E.; Riikonen, R.; Koponen, P.; Huhtala, H.; Helminen, M.; Korppi, M.; Nuolivirta, K.
Abstract: Background: Five studies carried out after bronchiolitis at less than 24 months of age, with a follow‐up of more than 10 years, reported that atopic dermatitis, family asthma, early‐life exposure to tobacco smoke and rhinovirus aetiology were early‐life risk factors for later asthma. This study evaluated the long‐term outcome at 11‐13 years of age of children who were hospitalized for bronchiolitis in early infancy. Methods: We previously prospectively followed 166 children hospitalized for bronchiolitis at less than 6 months of age until 5‐7 years of age. The current study included a structured questionnaire, parental interviews, clinical examinations and bronchodilation test of 138 of those children at 11‐13 years of age. Results: Respiratory syncytial virus caused 66% of the bronchiolitis cases, and nearly half of the patients were exposed to tobacco smoke in early life. Doctor‐diagnosed asthma was present in 13% of the former bronchiolitis patients at 11‐13 years of age. Maternal asthma was the only independently significant risk factor in early life (adjusted OR 3.45, 95% CI 1.07‐11.74), as was allergic rhinitis at 5‐7 years of age (adjusted OR 4.06, 95% CI 1.35‐12.25). Conclusions: After bronchiolitis at less than 6 months of age, the risk of doctor‐diagnosed asthma at 11‐13 years was about twice that of the general Finnish population. Maternal asthma was the only independently significant early‐life risk factor for current asthma at 11‐13 years of age.